m6A Modification in Non-Coding RNA: The Role in Cancer Drug Resistance - Chen, Chen; Guo, Yuying; Guo, Yaxin; Wu, Xiaoke; Si, Chaohua; Xu, Yanxin; Kang, Qiaozhen; Sun, Zhenqiang (Frontiers in Oncology, 2021)
Cancer drug resistance has always been a major difficulty in cancer therapy. In the face of drug pressure, resistant cancer cells show complex molecular mechanisms including epigenetic changes to maintain survival. Studies prove that cancer cells exhibit abnormal m6A modification after acquiring drug resistance. m6A modification in the target RNA including noncoding RNA can be a controller to determine the fate and metabolism of RNA by regulating their stability, subcellular localization, or translation. In particular, m6A modified non-coding RNA plays multiple roles in multiple drug-resistant cancer cells, which can be a target for cancer drug resistance. Here, we provide an overview of the complex regulatory mechanisms of m6A-modified non-coding RNA in cancer drug resistance, and we discuss its potential value and challenges in clinical applications.